Combined influence of teichoic acids from Staphylococcus aureus and heterometallik Cu/Cd ethylenediamine complex on peritoneal macrophages and tumor cells - Nikulina, V.V.; Garmanchuk, L.V.; Senchylo, N.V.; Nikolaenko, T.V.; Dzhus, O.I.; Ostapchenko, L.I.; Khranovska, N.M. (Цитология и генетика, 2014)
We investigated the effects of teichoic acid (TA) from Staphylococcus aureus Wood 46 on tumor growth and metastasis of the experimental Lewis lung carcinoma (LLC) in mice. Intranasal administration of TA alone aggravated both tumor growth and metastasis, whereas combined administration of TA with a synthetic bimetallic (copper: cadmium) ethylene diamine complex PO244 resulted in pronounced antitumor and antimetastatic effects. The group of animals subjected to the combined treatment with TA and PO244 manifested the highest degree of lymphocyte infiltration into the tumor tissue, compared to the control group and those exposed to TA or PO244 alone. Moreover, the combined treatment negatively affected the adhesive properties of peritoneal macrophages in the LLC bearing mice. Co-cultivation of the isolated macrophages with primary LLC cultures revealed significant (p < 0.05) cytotoxic and cytostatic effects, detected as an increased level of apoptosis and a reduced fraction of replicating cells. Исследовали модифицирующее влияние тейхоевой кислоты (ТК) на рост и метастазирование перевиваемой карциномы легких Льюис у мышей. Выявлена гиперактивация роста и метастазирования первичной опухоли при интраназальном введении животным ТК, в то время как при комбинированном влиянии с РО244 наблюдали усиление противо-опухолевого эффекта. Самый высокий уровень инфильтрации опухолевой ткани лимфоцитами зафиксировали в группе животных, которым проводили комбинированную терапию ТК с РО 244. Показано снижение адгезивных свойств перитонеальных макрофагов под влиянием биметаллического комплекса. После сокультивирования макрофагов от животных, которым проводили комбинированную терапию с первичной культурой LLC, выявлено значительное (p < 0.05) цитотоксическое/цитостатическое влияние, что проявлялось в увеличении уровня апоптоза и уменьшении популяции клеток пролиферативного пула.